Africa and the West: Between Tradition and Modernity in Shimmer Chinodya’s Dew in the Morning (1982) and Ngugi WA Thiongo’s weep Not, Child (1964) - Babacar DIAKHATÉ (Budapest International Research and Critics University, 2020)
European colonizers have impoverished Africans for spoiling their natural resources. African Anglophone writers such as Shimmer Chinodya and Ngugi WA Thiongo respectively in Dew in the Morning and Weep Not, Child devote most of their writings to land issues and cultural alienation. The aim of this article is to display the strategies of the White man to achieve his objective, and the contribution of his black collaborators to take Africans’ lands. It also reveals the importance of African traditional practices in the resistance against colonialism. Finally, it shows the perpetual quest of western education by Africans to “beat the white in his own game”.